Growing an artist : the story of a landscaper and his son - Parra, John (A Paula Wiseman Book, Simon & Schuster Books for Young Readers, 2022)
Today Juanito is accompanying his father who is in the landscaping business, and he takes his sketchbook along to draw anything that catches his eye, and gets to help his father plan an entire garden--and then help plant it. Includes an autobiographical note.